Histological Prostatitis and its Correlation with Prostate Specific Antigen Levels (Medical Forum Monthly, 2024)
Objectives: The aim of the study was to find a relationship between Prostate Specific Antigen levels and histological prostatitis in people belonging to our part of the world mainly Khyber Pakhtunkhwa and adjoining areas of Afghanistan.Study Design: Analytical / cross sectional studyPlace and Duration of Study: The study was conducted at the North West Hospital, Peshawar for a period of six months.Materials and Methods: A total of 200 patients who underwent surgical treatments for Benign prostatic hyperplasia due to obstructive or irritative symptoms were prospectively studied.Patients who complained of chronic pelvic pain or had a history of laboratory exam suggesting acute prostatitis were excluded.Results were analysed using Mann-Whitney rank sum test or Pearson product moment correlation (for Prostate specific antigen vs inflammation) at 95%CI.Results: In my study of the 200 cases, 98 cases with histological prostatitis had normal PSA levels and 102 cases with histological prostatitis had raised PSA levels. Of the cases with raised PSA levels , most cases were of grade I inflammation with multiple spread and their location was glandular, peri- glandular plus stromal.Conclusion: It is shown in numerous studies that there is a relationship between PSA levels and Histological Prostatitis .My study revealed that a relationship doesexist between PSAlevels and Prostatitis but it is a weak one.PSA levels can be raised in conditions other than prostatitis.